Institutional insights into contract theories: A comparative approach to the French and German dairy industries under liberalization - Marie Derville; Andrea Fink-Keßler (The European Journal of Comparative Economics (EJCE), 2019)
To analyse farmer market access following European dairy-market liberalization, this article provides a novel, institutional and spatially explicit approach to contract theory. Contractual reciprocal agreements, bargaining power, the regulatory framework, the regional market structure, quality differentiation and resource pooling are considered. The multi-scalar conceptual framework developed allows for shedding light on the value creation and sharing process in supply chains. A comparative case study highlights that market liberalization and contractual relations question the farmers' collective rights and responsibilities in supply chains and production basins. Depending on the regional production model, viable strategies differ; concentration and economies of scale is required for a generic market while specific quality or the provision of environmental services can support more diversified production models. Public policies can support farmers by endorsing large regional producer organizations and framework contracts and by favouring information transparency. CAP national and regional orientation is another manner by which to support the competitiveness of regional supply chains, but it questions the purpose of the "common" European policy.
Keywords: Q13; Q18; R11; D86; 330; contract; institutional framework; liberalization; market access; regional competition regime; European dairy industry; comparative analysis